ANALISIS PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENANGGULANGAN BENCANA DI KABUPATEN OGAN KOMERING ULU - Herni Ramayanti; Ahmad Zahrudin; A Zikri Mysata (Universitas Bandar Lampung (UBL), 2022)
In accordance with Article 8 of Law Number 24 of 2007, the Ogan Komering Ulu district must establish the Regional Disaster Management Agency (BPBD) at the provincial, district, and municipal levels to handle disasters. Regarding the issues raised, particularly What function does the Regional Disaster Management Agency (BPBD) serve in the Ogan Komering Ulu Regency's disaster management? The goal of this study was to ascertain the Regional Disaster Management Agency's (BPBD) function in Ogan Komering Ulu Regency's disaster management. This research approach uses descriptive qualitative theory to explain events based on field conditions and to characterize these phenomena by descriptive analysis on independent variables. ways for gathering data, including documentation, interviews, and observation. The findings of the study on how the Regional Disaster Management Agency (BPBD) handles disasters in the Ogan Komering Ulu Regency. It is clear that catastrophe management has been effectively maximized. This is evident in the initiatives implemented, namely in the areas of disaster prevention, readiness, early warning, mitigation, emergency response, rehabilitation, and reconstruction. This is implemented in a responsive manner as the Ogan Komering Ulu Regency's Regional Disaster Management Agency's role in disaster management.